The Influence of Financial Literacy and Digital Literacy on the Performance of Muhammadiyah-Owned MSMEs in Bandung City - Ikhsan Kamil; Budi Sadarman; Alia Tri Utami; Muhammad Najmi Dhaifullah; Muhamad Dzikry Raynan; Sintia Anggraeni (International Journal of Economics, Management and Accounting (IJEMA), 2026)
This study aims to analyze the influence of financial literacy and digital literacy on the performance of MSMEs owned by Muhammadiyah cadres in Bandung City. The study employed a quantitative approach with a survey method of 100 MSMEs selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of IBM SPSS Statistics 27. The results of the study indicate that financial literacy and digital literacy have a positive and significant impact on MSME performance. Simultaneously, both variables also significantly influence MSME performance. The Adjusted R Square value of 0.140 indicates that financial literacy and digital literacy can explain 14.0% of the variation in MSME performance, while the remainder is influenced by other factors outside the research model. The research findings indicate that improving financial management skills and utilizing digital technology are crucial aspects in supporting the performance of MSMEs. The findings are expected to provide input for Muhammadiyah organizations and stakeholders in designing programs to empower their cadres economically through strengthening financial and digital literacy.